“An Analysis of Trojan Horse Affairs, Measuring the Impact of Hoax Produced by Anti-Muslim Government in the UK” (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This paper highlights one concrete example of how the power of Hoaxes can provide an extra-ordinary significant impact to the country. The term of the Trojan Horse Affairs make this issue more interesting for the author to discuss. The term of Trojan Horse generally used in technological science to describe the existence of the malware or viruses activity, whos hiding in suspicious forms and then damage the core systems on a computer or steal its data. The damage caused by the Trojan Horse is usually very severe (Trojan Horses, 2019).In the study of international relations, the term of Trojan Horse was also recently introduced to defined the “terrorist operations”. This is because, terrorist operations are also use hidden movements on their actions to attack or stealing data which resulted in fatal damage. For that kind of reason, in the study of international relations, the term of Trojan Horse is also synonymous with serious crime, which are usually carried out by the opponents, enemies, or international criminal syndicate (Trojan Horses, 2019).Tracing the origin history the use of the term of The Trojan Horse will remind back with the Ancient Greek War, between the Achaena (Greek) and Trojan people. This history become phenomenal after the Achaena win the war with their clever trick of smuggling its soldier into an unsuspecting wooden horse statue, soon called “The Trojan Horse”statue. The Trojan people immediately got killed in the night, when their soldiers were unaware and sleeping. The Achenian soldiers came out from their hiding place and then ended this storys (Mogra, n.d.).